2013
DOI: 10.2478/pjvs-2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of egg yolk antibodies against bovine alimentary tract pathogens

Abstract: Aim of the study was to evaluate the effect of immunization of hens with bovine vaccines (C, R, T) on the course of IgY antibodies production against selected bovine E.coli strains, rota-and coronaviruses in egg yolk in farm conditions. The hens (40 individuals per group) were vaccinated twice, subcutaneously in four week interval and eggs were harvested once a week. Control group consisted of eggs sampled from non-vaccinated hens located in neighbouring cages. The antibody activity was measured by ELISA. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other studies performed to evaluate non-specific Ab as passive immunity against BCoV diarrhea show that calves treated with a milk replacement supplemented with commercial serum proteins (APC Lifeline with 10% immunoglobulins, 40% proteins, and 0.5% fat) resulted in no differences in diarrhea severity between the control and treated groups [ 48 ]. Finally, several researchers are studying IgY technology against CoV, but they did not evaluate the product in animal models [ 35 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies performed to evaluate non-specific Ab as passive immunity against BCoV diarrhea show that calves treated with a milk replacement supplemented with commercial serum proteins (APC Lifeline with 10% immunoglobulins, 40% proteins, and 0.5% fat) resulted in no differences in diarrhea severity between the control and treated groups [ 48 ]. Finally, several researchers are studying IgY technology against CoV, but they did not evaluate the product in animal models [ 35 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have previously described that prophylactic or therapeutic administration of hyperimmune egg yolk to newborn calves during the first days of life significantly reduced the severity of diarrhea after a challenge with virulent bovine RVA [ 25 , 26 ]. In contrast, there are just a few studies on BCoV prevention strategies for bovine and porcine species using IgY Abs [ 33 , 34 , 35 ]. There is only one study that reported that the administration of IgY Abs against BCoV in calves was efficacious against diarrhea [ 36 ].…”
Section: Introductionmentioning
confidence: 99%